The Effectiveness of Zondag Mandaag's Game on the Improvement of Basic Movement and Early Childhood Character - Pujiati, Sri; Kustiono, Kustiono (Universitas Negeri Semarang, 2020)
The lack of learning that stimulates basic movements and early childhood character. This is due to several things including the teacher's lack of understanding about the classification of basic movements and the environment that is less supportive. This study aimed to analyze the effectiveness of Zondag Mandaag game on improving basic movements and early childhood character. The experimental design that was carried out in this study was the True Experimental in the form of a Pretest-Posttest Control Group Design to analyze quantitative data on the effectiveness of the Zondag Mandaag game on improving basic movements and early childhood character. The result shows that there is an increase in basic movements and characters of early childhood after treatment with Zondag Mandaag games. It is evidenced by the average results of the first test is 58.83 in the experimental class and 58 in the control class, while the average score of the final test for the experimental class is 75.5 and 63.83 for the control class which shows an increase of 16.67 in experimental class and 5.85 in the control class. Thus, it can be concluded that the Zondag Mandaag’s game is effective in improving the basic movements and character of early childhood